High-strength chain steel, high-corrosion-resistance mine chain and manufacturing method of high-strength chain steel and high-corrosion-resistance mine chain

Through reasonable chemical composition design and hot coating and plating treatment process, the corrosion and stress sensitivity problems of mining chains in humid environments are solved, and high-strength, toughness and corrosion resistance are achieved, extending the service life.

CN119710484AActive Publication Date: 2025-03-28BAOSHAN IRON & STEEL CO LTD

Patent Information

Application Number
CN202311283446.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

Existing mining chains are susceptible to corrosion in humid environments, and high-strength chains have stress sensitivity, resulting in corrosion fatigue and fracture, and early failure.

Method used

Reasonable chemical composition design, including C, Si, Mn, Cr, Ni, Mo, Ti, Al, B and N elements, the hardenability and mechanical properties of steel are improved by adding elements B, the amount of expensive alloys is reduced, and the carbide structure with diffuse distribution between tempered martensite and sheet layer is formed by hot coating treatment.

Benefits of technology

It realizes the comprehensive performance of high-strength and high-toughness chains, has good corrosion resistance, and can maintain a long-term service life in a corrosive environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004479047020000121
    Figure BDA0004479047020000121
  • Figure BDA0004479047020000122
    Figure BDA0004479047020000122
  • Figure BDA0004479047020000123
    Figure BDA0004479047020000123
Patent Text Reader

Abstract

The invention discloses high-strength chain steel, a high-corrosion-resistance mine chain and a manufacturing method of the high-strength chain steel and the high-corrosion-resistance mine chain. The high-strength chain steel is prepared from the following chemical components in percentage by mass: 0.20 to 0.30 percent of C, 0.05 to 0.6 percent of Si, 1.0 to 1.8 percent of Mn, 0.4 to 0.8 percent of Cr, 0.6 to 1.2 percent of Ni, 0.5 to 0.9 percent of Mo, 0.01 to 0.03 percent of Ti, 0.02 to 0.05 percent of Al, 0.001 to 0.005 percent of B, 0.002 to 0.006 percent of N and the balance of iron and inevitable impurities. The high-corrosion-resistance mine chain has high strength and good corrosion resistance, and can be widely applied to environments with many corrosive media such as engineering machinery, mines, ships and ocean engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-strength chain steel and chains, and in particular to a high-strength chain steel and a high-corrosion-resistant mining chain and a manufacturing method thereof. Background Art

[0002] About 1 / 6 of the world's annual steel production is lost due to corrosion. The direct economic losses caused by steel corrosion in my country exceed 10 billion yuan each year. In addition, steel corrosion reduces the service life of steel structures, causes casualties and economic losses, and emissions cause environmental pollution. Mining round link chains are important components for mechanized coal mining in coal mines. They are mainly used as transmission chains on scraper conveyors, scraper transfer machines, coal mining machines and coal plows. They are required to have high strength and toughness, fatigue resistance, wear resistance and other properties during use. At present, the mining round link chain steel commonly used in the coal mining industry is usually the mining chain steel grade in "GB / T 10560-2017 Mining Welded Round Link Chain Steel". Among them, high-strength mining round link chain steel is mainly 23MnNiMoCr54 steel (referred to as 54 steel) and other grades are the most widely used. In response to the needs in actual applications, major domestic steel mills have also developed a series of high-strength mining chain steel according to the different needs of downstream users.

[0003] The Chinese patent with publication number CN110714164A and publication date January 21, 2020, entitled "A high-quality Cr54 steel for coal mine chain links and its production method", discloses a high-quality 54 steel for coal mine chain links, which introduces carbon equivalent, cold crack sensitivity coefficient, and hot crack sensitivity coefficient to ensure the welding performance of the chain steel and improve the cold and hot brittleness resistance of the chain steel.

[0004] The Chinese patent with publication number CN104532143A and publication date April 22, 2015, entitled "A large-size, high-strength mining chain steel and its manufacturing method", discloses an improved large-size mining chain steel with a diameter of Yield strength ≥980MPa, tensile strength ≥1180MPa, elongation ≥13%, section shrinkage ≥50%, room temperature Charpy impact energy>100J.

[0005] In addition, there are some technologies that optimize steel based on the composition of 54 steel. For example, the Chinese patent with publication number CN111101078A and publication date May 5, 2020, entitled "A nickel-free high-strength mining round link chain steel and its production method", discloses a high-strength mining round link chain steel that does not contain Ni. By reducing the alloy content of the precious metal element Ni and increasing the alloy element content of C, Si, Cr, and Mo, the production cost is greatly reduced while ensuring the mechanical properties.

[0006] Referring to the above-mentioned prior art and combining with many current improvement schemes, it is not difficult to find that researchers in this field mainly prepare higher-strength mining chain steel through component optimization design to improve the strength and wear resistance of the mining chain made of mining chain steel, so as to obtain a longer service life.

[0007] However, it should be noted that in actual application, coal mines are mostly working in a humid environment. High-strength mining chains are inevitably affected by environmental corrosion during use. In addition, high-strength mining chains have high stress and are more sensitive to stress corrosion. They are very likely to cause corrosion fatigue fractures during use (frequent low-load brittle fractures occur in as little as a few days or as many months), causing early failure of mining chains.

[0008] Based on this, the present invention hopes to obtain a new mining chain steel, which has excellent comprehensive performance. It not only has high strength, but also can achieve better high-strength and high-toughness properties with lower alloy cost. After coating and plating, the chain has excellent corrosion resistance, which can well solve the problem of existing mining chains affecting service life due to mismatch between strength and corrosion resistance. Summary of the invention

[0009] In view of the problem that the service life of existing mining chains in the prior art is affected by the mismatch between strength and corrosion resistance, the purpose of the present invention is to provide a high-strength chain steel and a high-corrosion-resistant mining chain and a manufacturing method thereof. The high-strength chain steel reduces the amount of expensive alloy added and is combined with a special coating process after the chain is made. It not only has good comprehensive properties such as high strength and high toughness, but also has good corrosion resistance. It can be widely used in environments with more corrosive media such as engineering machinery, mines, ships and marine engineering.

[0010] To achieve the above object, the present invention adopts the following technical solution:

[0011] The first aspect of the present invention provides a high-strength chain steel, comprising the following chemical components in percentage by mass: C: 0.20-0.30%, Si: 0.05-0.6%, Mn: 1.0-1.8%, Cr: 0.4-0.8%, Ni: 0.6-1.2%, Mo: 0.5-0.9%, Ti: 0.01-0.03%, Al: 0.02-0.05%, B: 0.001-0.005%, N: 0.002-0.006%, and the remainder is iron and unavoidable impurities.

[0012] Preferably, its composition meets the following requirements: 30000*B / (300*B+0.7*Ni+2*Cr+5*Mo)≥6.

[0013] Preferably, among the unavoidable impurities, P≤0.015%, S≤0.01%, and O≤0.002%.

[0014] Preferably, the austenite grain size of the high-strength chain steel is ≥ grade 7; after quenching heat treatment and hot-dip coating treatment, the microstructure of the high-strength chain steel is tempered martensite and carbides dispersedly distributed between lamellar layers.

[0015] Preferably, after heat treatment and hot-dip coating, the high-strength chain steel has the following properties: yield strength Rp 0.2 ≥1050MPa, tensile strength R m ≥1200MPa, elongation A≥14%, section shrinkage Z≥50%, -20℃ Charpy impact energy A kv ≥60J.

[0016] Preferably, after the surface of the high-strength chain steel is treated with hot-dip plating, the corrosion rate is ≤0.2g / m after a 5% NaCl neutral salt spray corrosion test for 120h. 2 .h.

[0017] The second aspect of the present invention provides a high corrosion resistant mining chain made of the high strength chain steel described in the first aspect of the present invention, the performance of which meets the following requirements: yield strength Rp 0.2 ≥1050MPa, tensile strength R m ≥1200MPa, elongation A≥14%, section shrinkage Z≥50%, -20℃ Charpy impact energy A kv ≥60J; After 120h of 5% NaCl neutral salt spray corrosion test, the corrosion rate is ≤0.2g / m 2 .h.

[0018] The third aspect of the present invention provides a method for manufacturing the highly corrosion-resistant mining chain according to the second aspect of the present invention, comprising the following steps:

[0019] S1, smelting and casting;

[0020] S2, hot rolling, control the compression ratio of the material ≥10;

[0021] S3, ring welding;

[0022] S4, quenching heat treatment, the heating temperature of the quenching heat treatment is 850-950°C, the holding time is 1-3h, and then water cooling quenching is adopted;

[0023] S5, pickling pretreatment;

[0024] S6, hot dip galvanizing, the chain after pickling pretreatment is preheated and then hot dip galvanized to obtain a high corrosion resistant mining chain, and the difference between the preheating temperature of the preheating treatment and the temperature of the galvanizing solution used for the hot dip galvanizing is controlled to be -30 to 30°C.

[0025] Preferably, in step S1, the smelting includes electric furnace or converter smelting, LF refining, VD or RH vacuum treatment; and the casting adopts a continuous casting process.

[0026] Preferably, the vacuum treatment time of the VD or RH vacuum treatment is 10 to 20 minutes; and the superheat of the molten steel in the tundish is controlled to be 15 to 40° C. during the casting process.

[0027] Preferably, in step S2, during the heating and rolling process, the heating temperature of the ingot is controlled to be ≥1150°C, the heating time is 3 to 6 hours, the final rolling temperature is ≥850°C, and air cooling or slow cooling is adopted after rolling.

[0028] Preferably, in step S6, the preheating temperature is 400-550°C, and the preheating time is ≥0.5h; and the temperature of the galvanizing solution used in the hot-dip galvanizing is 400-530°C.

[0029] Preferably, the thickness of the zinc layer on the surface of the highly corrosion-resistant mining chain is 10 to 150 μm.

[0030] Preferably, the microstructure of the highly corrosion-resistant mining chain is tempered martensite and carbides dispersedly distributed between lamellar layers.

[0031] Preferably, the performance of the high corrosion resistant mining chain meets the following requirements: yield strength Rp 0.2 ≥1050MPa, tensile strength R m ≥1200MPa, elongation A≥14%, section shrinkage Z≥50%, -20℃ Charpy impact energy A kv ≥60J; After 120h of 5% NaCl neutral salt spray corrosion test, the corrosion rate is less than 0.2g / m 2 .h.

[0032] In the high-strength chain steel of the present invention, the design principles of each chemical element are as follows:

[0033] C: In the high-strength chain steel of the present invention, C is an element necessary to ensure the strength of the steel. Increasing the C content in the steel will increase the non-equilibrium structural transformation ability of the steel, thereby significantly improving the strength of the steel; in the present invention, the diffusion of the C element in the steel can be suppressed by the quenching and tempering heat treatment process to form a shear-type martensitic phase transformation, thereby significantly improving the strength of the steel. However, the C content in the steel should not be too high. Too high a C content will have an adverse effect on the plasticity and toughness of the steel, and will significantly increase the carbon equivalent of the material, deteriorating the welding performance of the steel. Based on this, in the high-strength chain steel of the present invention, the mass percentage of the C element is controlled to be between 0.20 and 0.30%.

[0034] Si: In the high-strength chain steel of the present invention, the Si element can be dissolved in the steel and play a role of solid solution strengthening, which can significantly improve the yield strength, fatigue strength and hardness of the steel. The solubility of Si in cementite is very low, and the Si content in the steel should not be too high. When the Si content in the steel is too high, not only will a carbide-free bainite structure be formed, but the brittleness of the steel will also be increased. Based on this, in the high-strength chain steel of the present invention, the mass percentage of the Si element is controlled between 0.05 and 0.6%.

[0035] Mn: In the high-strength chain steel of the present invention, the Mn element can improve the stability of austenite in the steel, and at the same time improve the hardenability of the steel. In addition, Mn can also improve the strength of martensite in the steel through solid solution strengthening, thereby improving the strength of the steel. However, it should be noted that the Mn content in the steel should not be too high. When the Mn content in the steel is too high, the austenite grains will grow easily during quenching heating, and promote the segregation of harmful elements at the grain boundaries. Based on this, in the high-strength chain steel of the present invention, the mass percentage of the Mn element is controlled between 1.0 and 1.8%.

[0036] Cr: In the high-strength chain steel of the present invention, adding an appropriate amount of Cr element can improve the hardenability of the steel and has a secondary hardening effect. It can form a hardened martensitic structure, which is beneficial to improving the strength of the steel. In addition, Cr carbide can slow down the grain growth in the heat-affected zone at the welded joint, which is very beneficial for the welding of steel; adding an appropriate amount of Cr and Ni elements to the steel is beneficial to improving the corrosion resistance of the steel. However, the Cr content in the steel should not be too high. When the Cr content in the steel is too high, a large amount of carbides will be generated and aggregated at the grain boundaries, reducing the toughness of the material and significantly increasing the carbon equivalent, deteriorating the welding performance of the high-strength steel. Based on this, in the high-strength chain steel of the present invention, the mass percentage of the Cr element is controlled between 0.4 and 0.8%.

[0037] Ni: In the high-strength chain steel of the present invention, Ni, as one of the main strengthening elements, can exist in the steel in the form of solid solution and can be infinitely solid-solved with iron. When the Ni element is used in combination with the Cr element, the hardenability of the steel will be significantly improved. In addition, adding an appropriate amount of Ni element to the steel can also reduce the C content of the eutectic point, strengthen the ferrite and refine and increase the pearlite, which can improve the strength of the steel without significantly affecting the plasticity of the steel. The Ni element can improve the fatigue resistance of the steel, reduce the sensitivity of the steel to notches, reduce the low-temperature brittle transition temperature of the steel, and improve the impact toughness of the steel. Ni is a precious alloy element, and adding excessive Ni will lead to an increase in the alloy cost. In the high-strength chain steel of the present invention, the mass percentage of the Ni element is controlled between 0.6 and 1.2%.

[0038] Mo: In the high-strength chain steel of the present invention, the Mo element mainly exists in the steel in the form of solid solution, which can play a solid solution strengthening effect, which is beneficial to improve the hardenability of the steel and allows the steel to form martensite during the quenching process. However, the Mo content in the steel should not be too high. When the Mo content in the steel is too high, the carbon equivalent of the material will be significantly increased, which is not conducive to the welding performance of the steel; in addition, Mo is also a precious alloy element, and adding excessive Mo will also lead to an increase in alloy costs. Based on this, in the high-strength chain steel of the present invention, the mass percentage of the Mo element is controlled between 0.5 and 0.9%.

[0039] Ti: In the high-strength chain steel of the present invention, the Ti element has a strong affinity with nitrogen, oxygen, and carbon, and has a high precipitation temperature. It is an effective element that is good at fixing nitrogen and carbon. It forms a fine precipitate phase in the steel, which can improve the strength and toughness of the steel, especially the impact toughness at low temperatures. However, when the Ti content in the steel is too high, coarse and angular TiN particles will be formed during the smelting process, reducing the impact toughness of the steel. Therefore, in the high-strength chain steel of the present invention, the Ti content is controlled to: Ti≤0.01%.

[0040] Al: In the high-strength chain steel of the present invention, the main function of Al is deoxidation and nitrogen fixation. AlN formed by the combination of Al and N can effectively refine the grains. However, it should be noted that the Al content in the steel should not be too high. When the Al content in the steel is too high, it will affect the casting performance of the steel and damage the toughness of the steel. Based on this, in the high-strength chain steel of the present invention, the mass percentage of the Al element is controlled between 0.02 and 0.05%.

[0041] B: In the high-strength chain steel of the present invention, the main function of B is to increase the hardenability of the steel, improve the strength of the steel after quenching and tempering, and slightly improve the plasticity, thereby saving other relatively rare and precious metals, such as nickel, chromium, molybdenum, etc. However, the B element is relatively active, and it has a strong affinity with elements such as oxygen and nitrogen, and it is easy to form boron oxide, boron nitride, etc., which makes the B element ineffective, increases the fluctuation of the hardenability of the steel, and affects the stability of the steel performance. B is an active and easily segregated element, which is easy to segregate at the grain boundary, and will produce temper brittleness, which is not good for the toughness of the steel. Therefore, in the high-strength chain steel described in the present invention, the B element content is controlled to be: 0.001-0.005%

[0042] N: In the high-strength chain steel of the present invention, N is an austenite-forming element and also an MX-type precipitate-forming element, which plays a role in refining grains; in B-containing steel, the N element in the steel will combine with the B element, thereby causing the B in the steel to lose its alloying effect. In order to avoid the N element consuming the B element, the N element content in the steel must be strictly controlled. In the high-strength chain steel of the present invention, the mass percentage of the N element is controlled to be between 0.002 and 0.006%.

[0043] For the present invention, through the reasonable design of the main alloying elements, the hardenability and mechanical properties of the steel are improved by adding the B element, the addition amount of expensive alloys is reduced, and the influence of various alloying elements and their interactions on the microstructure and mechanical properties is fully utilized, so that the high-strength chain steel of the present invention has excellent comprehensive properties.

[0044] In a preferred implementation case, in the chemical composition of the high-strength chain steel, the substitution coefficient between the B element and the Cr, Ni, and Mo alloys satisfies:

[0045] 30000*B / (300*B+0.7*Ni+2*Cr+5*Mo)≥6;

[0046] In the high-strength chain steel of the present invention, Cr, Ni, and Mo elements are important alloying elements, and the contribution of each element to the toughness and hardenability of the chain steel is different. Excessive addition of expensive alloying elements will greatly increase the cost of the steel. Therefore, appropriate amounts of Cr, Ni, and Mo elements are added to the high-strength chain steel and interact with the addition of trace B elements to the steel. When the substitution coefficient between the B element and the Cr, Ni, and Mo alloy satisfies 30000*B / (300*B+0.7*Ni+2*Cr+5*Mo)≥6, the B element can be dissolved in the matrix, segregated at the austenite grain boundary, improve the stability of the austenite, increase the hardenability of the steel during the heat treatment of the chain, and make the steel have better comprehensive properties such as high strength and high toughness. When 30000*B / (300*B+0.7*Ni+2*Cr+5*Mo)<6, the content of B element added in the steel is low and cannot play a role in improving the hardenability of the steel. In order to ensure that the chain steel obtains better high strength and high toughness during the heat treatment process, expensive alloy elements must be added, which increases the chain production cost.

[0047] In the high-strength chain steel of the present invention, for the inevitable impurities, P≤0.015%, S≤0.01%, O≤0.002%. Among them, P element, S element and O element are all impurity elements in steel. Under the condition that technical conditions permit, in order to obtain high-strength chain steel with better performance and better quality, the content of impurity elements in the material should be reduced as much as possible. In the high-strength chain steel of the present invention, P element and S element are both inevitable harmful impurity elements in steel, and both will deteriorate the performance of steel. Although P element can improve the weather resistance of steel, in general, its side effects are greater. Therefore, in the present invention, P element is controlled to meet: P≤0.015%, and S element is controlled to meet: S≤0.01%. Correspondingly, in the present invention, impurity element O can form oxides and complex inclusions with deoxidizing elements such as Ti, B, Al in steel, which is not conducive to the performance of steel. Therefore, in the present invention, O element is controlled to meet: O≤0.002%.

[0048] Of course, in some other implementations, other harmful elements may exist in the steel, such as As, Pb, Sn, Sb, Bi and other elements. Under the requirements of national laws, regulations and standards, the content of these harmful elements should be reduced as much as possible.

[0049] Compared with the existing production technology, the present invention has the following beneficial effects:

[0050] 1. The present invention adopts a reasonable chemical composition design and cooperates with an optimized manufacturing method. The hardenability and mechanical properties of the steel are improved by adding the B element, the amount of expensive alloy added is reduced, and the influence of various alloy elements and their interactions on the microstructure and mechanical properties is fully utilized, so that the high-strength chain steel of the present invention has excellent comprehensive performance. Through the online quenching and hot-dip galvanizing treatment of the chain, on the one hand, fine carbides can be dispersed and precipitated in the supersaturated solid solution formed by quenching the chain steel, thereby improving the performance of the chain; at the same time, a zinc layer of a certain thickness can be formed on the surface of the chain, so that the chain has excellent corrosion resistance;

[0051] 2. After the zinc coating is applied to the surface of the chain, the present invention can isolate the corrosive medium from contacting the chain substrate, thereby improving the corrosion resistance of the chain; when the coating of a part of the chain area is worn, the zinc layer in other areas can also play an anode protection role, preventing corrosion from occurring during the use of the chain, thereby increasing the service life of the chain;

[0052] 3. The chemical composition and process design of the high-strength chain steel of the present invention are reasonable, the process window is wide, and batch commercial production can be achieved;

[0053] 4. The high-strength chain steel and chain of the present invention achieve excellent high strength and toughness and good corrosion resistance with relatively low composition. They can be made into high-strength and corrosion-resistant structural parts and various high-performance industrial chains such as mining and mooring, and are widely used in engineering machinery, mining and marine engineering, etc., where high-strength and high-toughness and high-corrosion-resistant steels are required;

[0054] 5. The high-strength chain steel of the present invention has high strength and toughness and plasticity after being made into high-corrosion-resistant mining chains, and also has excellent corrosion resistance, and its application prospects are very broad. DETAILED DESCRIPTION

[0055] In order to better understand the above technical solution of the present invention, the technical solution of the present invention is further described below in conjunction with embodiments.

[0056] The present invention provides a high-strength chain steel, comprising the following chemical components in percentage by mass: C: 0.20-0.30%, Si: 0.05-0.6%, Mn: 1.0-1.8%, Cr: 0.4-0.8%, Ni: 0.6-1.2%, Mo: 0.5-0.9%, Ti: 0.01-0.03%, Al: 0.02-0.05%, B: 0.001-0.005%, N: 0.002-0.006%, and the remainder is iron and unavoidable impurities.

[0057] The present invention improves the performance of the steel by adding the B element through reasonable design of the main alloy elements, reduces the amount of expensive alloy added, fully utilizes the influence of various alloy elements and the interaction between them on the microstructure and mechanical properties, and accurately controls the microstructure of the steel of the present invention to ensure that the high-strength chain steel of the present invention forms a mixed structure of tempered martensite + carbides dispersed between lamellae. This microstructure enables the high-strength steel of the present invention to have both high strength and toughness-plasticity matching, and has good wear resistance and fatigue resistance.

[0058] In a specific embodiment, the composition of the high-strength chain steel meets the following requirements:

[0059] 30000*B / (300*B+0.7*Ni+2*Cr+5*Mo)≥6;

[0060] In the present invention, Cr, Ni, and Mo are important alloying elements, and the contribution of each element to the toughness and hardenability of high-strength chain steel is different. Excessive addition of expensive alloying elements will greatly increase the cost of steel. Therefore, appropriate amounts of Cr, Ni, and Mo elements are added to the steel and interact with trace amounts of B elements added to the steel. When the substitution coefficient between the B element and the Cr, Ni, and Mo alloy satisfies 30000*B / (300*B+0.7*Ni+2*Cr+5*Mo)≥6, the B element can be dissolved in the matrix, segregated at the austenite grain boundary, improve the stability of austenite, increase the hardenability of the steel during the heat treatment of the chain, and make the steel have better comprehensive properties such as high strength and high toughness. When 30000*B / (300*B+0.7*Ni+2*Cr+5*Mo)<6, the content of B element added in the steel is low and cannot play a role in improving the hardenability of the steel. In order to ensure that the chain steel obtains better high strength and high toughness during the heat treatment process, expensive alloy elements must be added, which increases the chain production cost.

[0061] In the present invention, P, S and O are all impurity elements in steel. Under the condition that technical conditions permit, in order to obtain high-strength steel with better performance and better quality, the content of impurity elements in the material should be reduced as much as possible; wherein P and S are both unavoidable harmful impurity elements in steel, and both will deteriorate the performance of steel. Although P can improve the weather resistance of steel, its side effects are generally greater. Therefore, among the unavoidable impurities, P≤0.015% and S≤0.01%; correspondingly, the impurity element O can form oxides and complex inclusions with deoxidizing elements such as Ti, B, Al in steel, which are not conducive to the performance of steel. Therefore, O≤0.002%.

[0062] In a specific embodiment, the austenite grain size of the high-strength chain steel is ≥ grade 7, and after the high-strength chain steel is subjected to quenching heat treatment and hot-dip coating treatment, its microstructure is tempered martensite and carbides dispersedly distributed between lamellar layers.

[0063] After quenching heat treatment and hot-dip coating treatment, the high-strength mining chain steel has the following properties: yield strength Rp 0.2 ≥1050MPa, tensile strength R m ≥1200MPa, elongation A≥14%, section shrinkage Z≥50%, -20℃ Charpy impact energy A kv ≥60J.

[0064] After the surface of the high-strength mining chain steel is treated with hot-dip galvanizing, the corrosion rate is ≤0.2g / m after 120h of 5% NaCl neutral salt spray corrosion test. 2 .h.

[0065] The present invention provides a high corrosion resistant mining chain made of the above high strength chain steel, the performance of which meets the following requirements: yield strength Rp 0.2 ≥1050MPa, tensile strength R m ≥1200MPa, elongation A≥14%, section shrinkage Z≥50%, -20℃ Charpy impact energy A kv ≥60J; After 120h of 5% NaCl neutral salt spray corrosion test, the corrosion rate is ≤0.2g / m 2 .h.

[0066] The present invention also provides a method for manufacturing the above-mentioned high corrosion-resistant mining chain, which is simple to produce, and the obtained high-strength steel chain has excellent high strength and toughness and good corrosion resistance;

[0067] The method for manufacturing the high-strength chain steel and the high-corrosion-resistant mining chain of the present invention specifically comprises the following steps:

[0068] S1, smelting and casting;

[0069] Specifically, the smelting operation includes electric furnace or converter smelting, LF refining, VD or RH vacuum treatment; that is, smelting is carried out in an electric furnace or converter, and LF refining, VD or RH vacuum treatment is performed, wherein the vacuum treatment time is 10 to 20 minutes, and the steel is tapped for casting after the chemical composition meets the requirements of high-strength chain steel; accordingly, in the casting process, a continuous casting process is adopted to cast the ingot, and the superheat of the molten steel in the tundish is controlled at 15 to 40°C, so as to finally obtain the ingot whose chemical composition meets the requirements of high-strength chain steel.

[0070] S2, hot rolling, control the compression ratio of the material ≥10;

[0071] Specifically, the ingot is heated in a heating furnace, and then taken out of the furnace and dephosphorized by high-pressure water before rolling. The ingot is rolled to obtain round steel of finished size, i.e., high-strength chain steel. The heating temperature of the ingot is controlled to be ≥1150°C, the heating time is 3 to 6 hours, and the final rolling temperature is ≥850°C; after rolling, it is air-cooled or slowly cooled to room temperature; wherein, during the rolling process, the material compression ratio is controlled to be ≥10; the finished size specification of the high-strength chain steel is Φ30 to 150mm.

[0072] S3, Ring Welding: High-strength chain steel is cut into fixed lengths and braided into single rings on a braiding machine and then flash welded into a complete ring chain.

[0073] S4, quenching heat treatment, the heating temperature of quenching heat treatment is 850-950℃, the holding time is 1-3h, and the chain is water-cooled after heating;

[0074] Specifically, the ring-welded chain is subjected to quenching heat treatment, the heating temperature of the quenching heat treatment is 850-950°C, the holding time is 1-3h, and then water-cooling quenching is performed; when the chain is heated at high temperature, fine austenite grains are formed in the steel, and the austenite grain size is ≥ level 7; after quenching, the chain structure is transformed from the austenite structure at high temperature to a fine needle-shaped martensite structure.

[0075] S5, pickling pretreatment: The chain after quenching heat treatment is pickled for pretreatment to remove the oxide scale on the surface of the chain after quenching, and a layer of plating solution is applied on the surface of the chain to keep the surface of the chain after pickling to a certain activity, avoid oxidation of the chain during the subsequent preheating treatment, and enhance the bonding strength between the galvanized layer and the substrate.

[0076] S6, hot dip galvanizing, the chain after pickling pretreatment is preheated and then hot dip galvanized to obtain a high corrosion resistant mining chain, and the temperature difference between the preheating temperature of the preheating treatment and the galvanizing solution used for hot dip galvanizing is controlled to be -30 to 30°C.

[0077] Specifically, in order to prevent problems such as zinc explosion during hot-dip galvanizing, the chain is preheated after pickling pretreatment and then hot-dip galvanized to obtain a highly corrosion-resistant mining chain; the temperature difference between the preheating temperature of the chain and the galvanizing solution used in hot-dip galvanizing is controlled to be -30 to 30°C; wherein, the preheating temperature is 400 to 550°C, and the preheating time is ≥0.5h; the temperature of the galvanizing solution used in hot-dip galvanizing is 400 to 530°C, and the thickness of the zinc layer on the surface of the highly corrosion-resistant mining chain is controlled to be 10 to 150μm.

[0078] During the hot-dip galvanizing process, the supersaturated martensite structure formed after quenching of the chain begins to precipitate fine carbides, the strength of the chain decreases, but the elongation and impact toughness begin to increase. The fine martensite needle length is conducive to the precipitation of fine dispersed carbides from the steel during hot-dip galvanizing, obtaining a high-strength chain with excellent strength and toughness.

[0079] The microstructure of the above-mentioned high corrosion-resistant mining chain is tempered martensite and carbides dispersedly distributed between lamellar layers.

[0080] The performance of the above-mentioned high corrosion resistant mining chain meets the following requirements: yield strength Rp 0.2 ≥1050MPa, tensile strength R m ≥1200MPa, elongation A≥14%, section shrinkage Z≥50%, -20℃ Charpy impact energy A kv ≥60J; After 120h of 5% NaCl neutral salt spray corrosion test, the corrosion rate is less than 0.2g / m 2 .h.

[0081] The present invention makes full use of the influence of various alloy elements and the preparation process of high-corrosion-resistant mining chains on the microstructure through reasonable design of alloy elements and optimized preparation process, and accurately controls the microstructure of high-strength chain steel. After quenching heat treatment, the high-strength chain steel forms a needle-shaped martensite structure. Through hot-dip galvanizing of the quenched chain, on the one hand, fine and dispersed carbides can be precipitated during hot-dip galvanizing of the chain steel, thereby improving the toughness of the chain; at the same time, a zinc layer of a certain thickness can be formed on the surface of the chain, thereby improving the corrosion resistance of the chain.

[0082] In the chain preparation process of the present invention, the quenching and tempering process of the traditional chain is combined with the hot-dip galvanizing process, the tempering process of the chain is omitted, and the chain is fully utilized during the hot-dip galvanizing process to realize the precipitation of carbides in the steel, thereby realizing the efficient production of high-strength and corrosion-resistant chains, so that the high-strength chain steel has both high strength and toughness-plasticity matching, and has good corrosion resistance.

[0083] The high-strength chain steel and high-corrosion-resistant mining chain and their manufacturing method of the present invention are further introduced below with reference to specific examples.

[0084] Example

[0085] In combination with Table 1, Table 2-1 and Table 2-2, the high-strength chain steel and high-corrosion-resistant mining chain of Examples 1-6 adopt the following steps:

[0086] (1) Smelting and continuous casting are performed according to the chemical composition shown in Table 1 below to obtain ingots. The smelting can be performed by electric furnace or converter smelting, and then LF refining and VD or RH vacuum treatment are performed. The vacuum treatment time is 10 to 20 minutes. After the composition meets the requirements, the steel is tapped and then continuously cast into ingots. During the continuous casting process, the superheat of the molten steel in the tundish is controlled to be 15 to 40°C.

[0087] (2) Heating rolling: The ingot is heated in a heating furnace and then dephosphorized by high-pressure water before being processed into round steel of finished size, i.e., high-strength chain steel. The size of the rolled product is in the range of Φ30 to 150 mm, and the material compression ratio is controlled to be ≥10. During the rolling process, the ingot is heated and then rolled into the finished size. The heating temperature of the ingot is controlled to be ≥1150°C, the heating time is 3 to 6 hours, and the final rolling temperature is ≥850°C; after rolling, it is air-cooled or slowly cooled to room temperature.

[0088] (3) Ring welding: The high-strength chain steel is cut into round steel of fixed length and braided into a single ring on a braiding machine, and then flash welded into a complete ring chain.

[0089] (4) Quenching heat treatment: The chain after ring welding is quenched and heat treated, the heating temperature of the quenching heat treatment is controlled to be 850-950°C, the holding time is 1-3h, and then water-cooled quenching is performed.

[0090] (5) Pickling pretreatment: Pickle the chain after quenching to remove the oxide scale on the chain surface; then preheat the chain after pickling to prevent problems such as zinc explosion during the subsequent hot-dip galvanizing process. The chain preheating temperature is 400-550°C, the preheating time is ≥0.5h, and the temperature difference between the chain preheating temperature and the galvanizing solution used for subsequent hot-dip galvanizing is not higher than ±30°C.

[0091] (6) Hot dip galvanizing: The preheated chain is hot dip galvanized at a temperature of 400-530°C and the thickness of the zinc layer on the chain surface is controlled to be 10-150 μm.

[0092] The chemical composition design and related processes of the high-strength chain steel and high-corrosion-resistant mining chain of Examples 1 to 6 all meet the design specification requirements of the present invention. The comparative steels of Comparative Examples 1 to 2 are finished steels from different manufacturers, and their chemical composition designs can be seen in Table 1 below. Their processing technology is different from the preparation technology of Examples 1 to 6. The heat treatment process used for the comparative steels of Comparative Examples 1 to 2 refers to the parameters recommended by the supplier, and the specific values ​​are shown in Tables 2-1 and 2-2.

[0093] Table 1 Chemical composition of chain steel (wt.%, the balance is Fe and other impurities except P and S)

[0094]

[0095] Table 2-1 Process parameters of the examples and comparative examples during the preparation process

[0096]

[0097] Table 2-2 Process parameters in the preparation process of the embodiments and comparative examples

[0098]

[0099] The finished chains of Examples 1-6 that have been subjected to coating and plating treatment and the comparative chains of Comparative Examples 1-2 were collected, and their performances were further tested to obtain the performances of the finished chains of each Example and Comparative Example.

[0100] In the present invention, the high-strength steels of Examples 1-6 and the comparative steels of Comparative Examples 1-2 can be subjected to neutral salt spray corrosion test, tensile test and impact performance test, respectively, and the test results are listed in Table 3.

[0101] The specific detection methods for relevant neutral salt spray corrosion test, tensile test and impact test are as follows:

[0102] (1) The neutral salt spray corrosion test is carried out by the following steps: 100 mm long round steel is taken from the finished chain of Example 1-6 and the chain of Comparative Example 1-2 after coating as a salt spray corrosion specimen, and both end faces are sealed with silicone rubber. A 5 wt.% NaCl salt spray corrosion test is carried out according to GB / T10125 standard (laboratory temperature 35°C, saturated barrel temperature 47°C, corrosive medium is 5 wt.% NaCl aqueous solution, pH=6.5, the test sample is at an angle of 20° in the longitudinal direction, the test time is 120 h, continuous spraying is adopted, and the salt spray deposition amount is 1.5 mL / (h·80 cm 2 )). After the 120h neutral salt spray test, the test sample was taken out, the silicone rubber at both ends was peeled off, the surface corrosion products were removed, the sample was blown dry and the mass was weighed and recorded as M', and then the salt spray corrosion rate R of each embodiment and comparative example sample was calculated:

[0103] R=(M-M') / (S·T)

[0104] Where M is the initial mass of the sample, with the dimension of g; M' is the mass of the sample after the corrosion products are removed and blown dry, with the dimension of g; S is the corrosion test area of ​​the sample, with the dimension of m 2 ; T is the corrosion time, the dimension is h; the salt spray corrosion rate R is g / m 2 .h.

[0105] Tensile test: The finished chains of Examples 1-6 and the chains of Comparative Examples 1-2 were sampled and made into tensile specimens according to the national standard GB / T 2975, and the tensile performance test was carried out according to the national standard GB / T 228.1 to measure the yield strength Rp of the finished chains of Examples 1-6 and the chains of Comparative Examples 1-2. 0.2 , tensile strength R m , elongation A and section shrinkage Z.

[0106] Impact test: The finished chains of Examples 1-6 and Comparative Examples 1-2 were sampled and made into impact specimens according to the national standard GB / T 2975, and the impact performance test was carried out according to the national standard GB / T 229 to measure the low-temperature impact energy A of the finished chains of Examples 1-6 and Comparative Examples 1-2. kv .

[0107] Table 3 Performance of the chains of the embodiments and comparative examples

[0108]

[0109]

[0110] As shown in Table 3, the high corrosion-resistant mining chains in Examples 1-6 of the present invention have excellent comprehensive performance, and their yield strength Rp 0.2 Between 1076 and 1185 MPa, the tensile strength R m Between 1212 and 1315 MPa, elongation A ≥ 14%, section shrinkage Z ≥ 50%, -20℃ Charpy impact energy A kv ≥60J. The neutral salt spray corrosion rate of the high corrosion resistant mining chain in Examples 1-6 is ≤0.19g / m 2 .h, which is much lower than the neutral salt spray corrosion rate of the comparison chain in Comparative Example 1-2. It can be seen that the corrosion resistance of the high-strength chain steel of the present invention after heat treatment and hot-dip galvanizing is significantly better than the existing comparison steel selected in Comparative Example 1-2.

[0111] From the above, it can be seen that the present invention can obtain a high-corrosion-resistant mining chain with excellent performance by combining a reasonable chemical composition design and a chain heat treatment and a subsequent galvanizing process to form an optimized quenching heat treatment and hot-dip galvanizing process. The high-strength chain steel of the present invention has excellent comprehensive performance. It not only has high strength, but also has excellent toughness-plasticity matching. After being made into a mining chain, it has excellent corrosion resistance and can well solve the problem of the existing mining chain that the service life is affected by the mismatch of strength, toughness-plasticity and corrosion resistance. The high-strength chain steel can be made into various high-performance industrial chains such as mining and mooring, and is widely used in construction machinery, mining, marine engineering and other occasions that require high-strength, high-toughness and high-corrosion-resistant chains.

[0112] It should be noted that those skilled in the art should recognize that the above embodiments are only used to illustrate the present invention and are not intended to limit the present invention. As long as they are within the spirit of the present invention, any changes or modifications to the above embodiments will fall within the scope of the claims of the present invention.

Claims

1. A high-strength chain steel, characterized in that: It includes the following chemical components in mass percentage: C: 0.20-0.30%, Si: 0.05-0.6%, Mn: 1.0-1.8%, Cr: 0.4-0.8%, Ni: 0.6-1.2%, Mo: 0.5-0.9%, Ti: 0.01-0.03%, Al: 0.02-0.05%, B: 0.001-0.005%, N: 0.002-0.006%, and the balance is iron and unavoidable impurities.

2. The high-strength chain steel according to claim 1, characterized in that: Its composition meets the following requirements: 30000*B / (300*B+0.7*Ni+2*Cr+5*Mo)≥6.

3. The high-strength chain steel according to claim 1, characterized in that: Among the unavoidable impurities, P≤0.015%, S≤0.01%, and O≤0.002%.

4. The high-strength chain steel according to claim 1, characterized in that: The austenite grain size of the high-strength chain steel is ≥ grade 7; after quenching heat treatment, the microstructure of the high-strength chain steel is tempered martensite and carbides dispersedly distributed between lamellar layers.

5. The high-strength chain steel according to claim 1, characterized in that: After quenching heat treatment, its performance meets the following requirements: yield strength Rp 0.2 ≥1050MPa, tensile strength R m ≥1200MPa, elongation A≥14%, section shrinkage Z≥50%, -20℃ Charpy impact energy A kv ≥60J.

6. The high-strength chain steel according to claim 1, characterized in that: After the surface of the high-strength chain steel is treated by hot plating, the corrosion rate is ≤0.2g / m after 120h of 5% NaCl neutral salt spray corrosion test. 2 .h.

7. A high corrosion-resistant mining chain made of the high-strength chain steel according to any one of claims 1 to 6, characterized in that: Its performance meets: yield strength Rp 0.2 ≥1050MPa, tensile strength R m ≥1200MPa, elongation A≥14%, section shrinkage Z≥50%, -20℃ Charpy impact energy A kv ≥60J; After 120h of 5% NaCl neutral salt spray corrosion test, the corrosion rate is ≤0.2g / m 2 .h.

8. A method for manufacturing a highly corrosion-resistant mining chain as claimed in claim 7, characterized in that: The following steps are involved: S1, smelting and casting; S2, hot rolling, control the compression ratio of the material ≥10; S3, ring welding; S4, quenching heat treatment, the heating temperature of the quenching heat treatment is 850-950°C, the holding time is 1-3h, and then water cooling quenching is adopted; S5, pickling pretreatment; S6, hot dip galvanizing, the chain after pickling pretreatment is preheated and then hot dip galvanized to obtain a high corrosion resistant mining chain, and the difference between the preheating temperature of the preheating treatment and the temperature of the galvanizing solution used for the hot dip galvanizing is controlled to be -30 to 30°C.

9. The method for manufacturing a highly corrosion-resistant mining chain according to claim 8, characterized in that: In the step S1, the smelting includes electric furnace or converter smelting, LF refining, VD or RH vacuum treatment; the casting adopts a continuous casting process, wherein the vacuum treatment time of the VD or RH vacuum treatment is 10 to 20 minutes; the superheat of the molten steel in the tundish is controlled to be 15 to 40° C. during the casting process; and / or In step S2, during the heating and rolling process, the heating temperature of the ingot is controlled to be ≥1150°C, the heating time is 3-6h, the final rolling temperature is ≥850°C, and air cooling or slow cooling is adopted after rolling; and / or In the step S6, the preheating temperature is 400-550°C, and the preheating time is ≥0.5h; the temperature of the galvanizing solution used in the hot-dip galvanizing is 400-530°C.

10. The method for manufacturing a highly corrosion-resistant mining chain according to claim 8, characterized in that: The thickness of the zinc layer on the surface of the high corrosion-resistant mining chain is 10 to 150 μm.

11. The method for manufacturing a highly corrosion-resistant mining chain according to claim 8, characterized in that: The microstructure of the high corrosion-resistant mining chain is tempered martensite and carbides dispersedly distributed between lamellar layers.

12. The method for manufacturing a highly corrosion-resistant mining chain according to claim 8, characterized in that: The performance of the high corrosion resistant mining chain meets the following requirements: yield strength Rp 0.2 ≥1050MPa, tensile strength R m ≥1200MPa, elongation A≥14%, section shrinkage Z≥50%, -20℃ Charpy impact energy A kv ≥60J; After 120h of 5% NaCl neutral salt spray corrosion test, the corrosion rate is less than 0.2g / m 2 .h.

Citation Information

Patent Citations

  • Mining large-specification and high-strength chain steel and preparation method thereof

    CN104532143A

  • Cr54 steel for high-quality coal mine chain ring and production method thereof

    CN110714164A

  • Nickel-free high-strength mining circular ring chain steel and production method thereof

    CN111101078A

  • High-intensity and corrosion-resistant Pb-Sn composite coating binding band and production method thereof

    CN104097848A

  • Mooring chain steel and mooring chain

    JP2019127636A

Cited By

  • 1400 MPa-grade ultrahigh-toughness mining chain ring steel and manufacturing method thereof

    CN121295000A